A microcontroller based microfluidic biochip for calcium percentage detection in blood - Zaid H. Al-Sawwaff; Zahraa M. Rashid; Mohammed Faeik Ruzaij Al-Okby; Fatma Kandemirli (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Apheresis is an essential step in clinical diagnostic. Searching for a safe and fast way was necessary to avoid wasting time and obtain the desired results efficiently. This research includes two stages: First, a microfluidic biochip with the properties of fast processing response, automation capability, and low-cost was designed having a tiny mesh-type channel that filters pure plasma from the blood components and a straight channel to deliver the pure plasma to a tank. Second, an automated system was designed to detect blood calcium levels using a microcontroller and a colors-detection sensor TCS3200-DB. The device is designed to take a 0.15 to 2.15 mg/dL, 10-160 µm blood sample, which is considered small compared to the samples taken for the blood apheresis process used in laboratories where a substantial quantity of pure plasma is obtained naturally. Pure plasma is mixed with calcium detectors R1 and R2 to get a violet-colored solution with a wavelength between 390 nm to 440 nm. The results of the proposed device were compared with the traditional methods used spectroscopy method using concentrations of 10 different blood samples, and the results proved that there is a slight error between the two processes.